2016
DOI: 10.1109/tpel.2015.2453631
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of Boundary and Hybrid Controllers for Indirect Energy Transfer Converters

Abstract: In boost converters and other indirect energy transfer topologies, transient-oriented controllers are designed to facilitate a dynamic response that may range from minimum time up to minimum output voltage deviation. Since analytical definitions for these control laws can become quite complex, a large-signal stability verification is not immediate. This paper explores the existence of stability of indirect energy transfer converters that are controlled by either boundary or hybrid controllers and introduces a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In a system with a single active boundary, a necessary condition is that σ(x) must divide the equilibrium points such that switch action always forces trajectories toward the boundary. More details about conditions for stability are presented in [151], with extensive analysis and discussion of nonlinear boundaries in [152]. It is clear how a conditional control law might apply to a system with a single active switch, but more complicated structures or multiple structures can be employed to govern the action of multiple switches.…”
Section: A Geometric Control Methods In Dc-dc Convertersmentioning
confidence: 99%
“…In a system with a single active boundary, a necessary condition is that σ(x) must divide the equilibrium points such that switch action always forces trajectories toward the boundary. More details about conditions for stability are presented in [151], with extensive analysis and discussion of nonlinear boundaries in [152]. It is clear how a conditional control law might apply to a system with a single active switch, but more complicated structures or multiple structures can be employed to govern the action of multiple switches.…”
Section: A Geometric Control Methods In Dc-dc Convertersmentioning
confidence: 99%
“…Different control schemes such as adaptive control [30,31], boundary layer control [32,33], model predictive control [34,35] and time-delayed robust controller [36], have been utilized to achieve the desired performance. However, these techniques are parameter dependent.…”
Section: Inner Control Loopmentioning
confidence: 99%
“…However, these methods are system dependent and add complexity to the design. It is reported that the performance improvement is achieved by using boundary layer control [27][28][29], adaptive nonlinear control [30], model predictive control [31][32][33], and a time delayed based robust controller [34]. However, these techniques are not completely parameter independent and require some knowledge of the system specifications like inductance of the coil and capacitance of the filter stage.…”
Section: Introductionmentioning
confidence: 99%